Contempt of religions between restricting and unleashing freedom of expression: A legal reading of the provisions of international human rights law and the provisions of Islamic law - Hesham bin Abdulmalik bin Dehaish (International Journal of Law Research and Studies, 2025)
This research paper presents the hypothesis related to studying the restriction of the right to freedom of expression regarding expressions containing contempt for and defamation of religions. Western ideology views such expressions as freedom of expression because they are not related to individual freedom, despite the fact that this ideology adopts restrictions on expressions containing Holocaust denial and hate speech. It is worth noting that these expressions are governed by a single legal basis, which makes the hypothesis of a dispute between "Western liberalism and the provisions of Islamic Sharia" baseless and unfounded in fact and law.The present study refutes these claims, which claim that contempt for religions is permitted by law according to international human rights documents, and that Western societies have similar laws that do not cause such controversy. The difference between these Islamic and Western laws is the result of the philosophical, cultural, and legal perspectives on the concept and content of public morality in societies and states. Hence, since international human rights law allows for the restriction of rights in the name of public morality, differences in the content of public morality necessarily lead to differences in the content of those rights granted. Therefore, the compatibility between the law of contempt and defamation of religions and human rights in the West confirms that Islamic law and international human rights law agree, in principle, and differ in detail.
Keywords: Contempt of Religions; Defamation of Religion; Restriction of Freedom of Expression; Islamic Law; International Human Rights Law